Internal Self-Determination and the Post-Colonial State: The Chittagong Hill Tracts in International Law - A Z M Umar Faruque Siddiki (Law and Policy Review, 2025)
In international law, the nexus between self-determination and minority rights is persistently disputed, giving rise to a durable conflict between the prerogatives of state sovereignty and the entitlements asserted by internal groups. This challenge became acute in the post-WWII era with the emergence of the internal self-determination doctrine, which frames self-determination as a continuous right to political participation, distinct from external self-determination (secession). This paper critically examines how states and international bodies have articulated this internal dimension within the volatile context of post-colonial statehood. Using the case study of the Chittagong Hill Tracts (CHT) in Bangladesh, it analyzes the marginalization of ethnic minorities’ rights amidst state-building processes. The study specifically investigates the impact of state-sponsored Bengali settlement on the region’s demographic and rights equilibrium, arguing that such policies have systematically undermined the minority’s claim to meaningful self-determination and exacerbated political instability.